The Influence of a Differentiated Approach on Interest and Learning Outcomes in Shot Put - Agriansya, Deni; Rosani, Meilia; Imansyah, Farizal (PPSDP International Journal of Education, 2024)
This research aims to determine the effect of a differentiated approach on interest and learning outcomes in shot put at SMAN 1 Talang Ubi. This research is a type of quantitative research with a quasi-experimental design type The Nonequivalent Control Group Design. The population in this study was class X at SMAN 1 Talang Ubi which consisted of four classes, namely classes X.1, The selection of research subjects used purposive sampling. Data was collected using questionnaires to determine students’ interest in learning and tests to determine learning outcomes in shot put. Data were analyzed using t-test. The results of this research show that there is an influence of the differentiated approach on (1) interest in learning shot put and (2) learning outcomes in shot put.